EBOLA Ag K-SeT rapid test: field evaluation in Sierra Leone. (June 2018) - Colavita, F.; Biava, M.; Mertens, P.; Gilleman, Q.; Borlon, C.; Delli Guanti, M.; Petrocelli, A.; Cataldi, G.; Kamara, A.T.; Kamara, S.A.; Konneh, K.; Vincenti, D.; et al.
Abstract: Objectives: Efficient interruption of Ebola virus disease (EVD) transmission chains critically depends on reliable and fast laboratory diagnosis. We evaluated the performance of the EBOLA Virus Antigen Detection K -SeT (EBOLA Ag K -SeT), a new rapid diagnostic antigen test in field settings. Methods: The study was conducted in a field laboratory located in Freetown (Sierra Leone) by the Italian National Institute for Infectious Diseases 'L. Spallanzani' and the EMERGENCY Onlus NGO. The EBOLA Ag K -SeT was tested on 210 residual plasma samples (EVD prevalence 50%) from patients hospitalized at the EMERGENCY Ebola treatment center in Goderich (Freetown), comparing the results with quantitative real-time PCR. Results: Overall, the sensitivity of EBOLA Ag K -SeT was 88.6% (95% confidence interval (CI), 82.5–94.7), and the corresponding specificity was 98.1% (95% CI, 95.5–100.7). The positive and negative predictive values were 97.9% (95% CI, 95.0–100.8) and 89.6% (95% CI, 84–95.2), respectively. The sensitivity strongly increased up to 98.7% (95% CI, 96.1–101.2) for those samples with high virus load (≥6.2 log RNA copies/mL). Conclusions: Our results suggest that EBOLA Ag K -SeT could represent a new effective diagnostic tool for EVD, meeting a need for resource-poor settings and rapid diagnosis for individuals with suspected EVD.